Pengaruh Celebrity Endorser Terhadap Keputusan Pembelian Pada Zenius Education (Survei Pada Komunitas Online Zenius Education) - Shabrina, Hasna Nur; Batu, Reminta Lumban (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2020)
Zenius is a creation of Indonesian children in the world education. Zenius was built as a technology company which is focused on education services. Zenius Education was founded in 2004 as an offline tutoring, in 2007 it was inaugurated as PT Zenius Education and in 2010 as an online tutoring. The purpose of this study was to determine the effect of celebrity endorser on purchasing decisions at Zenius Education. This research was conducted using descriptive and verification methods. This research is a quantitative census research. The population in this study is Instagram followers of Zenius Education. This study is used the type of primary data and secondary data. Data is processed using path analysis with Partial Least Square (PLS). The results show that celebrity endorsers have an influence on purchasing decisions.